A Psoas Abscess Secondary to Urinary Tract Infection - Özen, Metehan; Arslan, Selda; Güngör, Serdal; Baysal, Tamer (Fırat University, 2006)
Diagnosis and management of psoas abscess is usually delayed as it is a rare entity in childhood period. Mortality is seriously high in case of delayed diagnosis and inappropriate therapy. We herewith present a female patient who was admitted with the symptoms of pain on the right side and legs, difficulty in walking and high fever. She was hospitalized with presumed diagnosis of perirenal hematoma, but finally diagnosed as psoas abscess secondary to urinary tract infection by the help of invasive techniques. We would like to emphasize the paramount importance of appropriate radiology methods in order to diagnose and treat the psoas abscess. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Psoas absesi çocukluk döneminde nadir görülen, tanısı zor ve geç konulan bir hastalıktır. Tanı ve tedavinin gecikmesi veya abse drenajının yapılmadığı durumlarda mortalite %100'e ulaşmaktadır. Bu yazıda, sağ yan tarafında ve bacaklarında ağrı, yürümede zorlanma ve ateş yüksekliği ile başvuran bir kız olgu sunulmuştur. Olgumuz perirenal hematom öntanısı ile yatırılarak takip edilmiş, ancak yapılan ileri tetkikler sonucunda idrar yolu enfeksiyonuna sekonder gelişen psoas absesi olduğu öğrenilmiştir. Sonuç olarak, psoas absesi olan hastaların sağaltımında girişimsel radyolojik yöntemlerin erken dönemde kullanılmasının ve abse drenajının en önemli faktör olduğu vurgulanmaktadır. ©2006, Fırat Üniversitesi, Tıp Fakültesi
İdrar Yolu Enfeksiyonuna Sekonder Gelişen Bir Psoas Abse Olgusu